Pengaruh Pemberian Arang Aktif dan Air Kelapa Terhadap Viabilitas Hasil Enkapsulasi Tunas Tetrastigma Rafflesiae Miq. - Dina Hayati Putri; - Suwirmen; Tesri Maideliza (Jurnal Biologi Universitas Andalas, 2014)
An experimental study to figure out the effect of activated charcoal and coconut water to shoot encapsulation of Tetrastigma rafflesiae Miq. has been carried out from October 2013 to February 2014 at Plant Physiology Laboratory, Biology Department, Faculty of Sciences, Andalas University. The experiment used Completely Randomized Design with four treatments and six replications. Treatments consisted of 1g/L activated charcoal, 300 mL/L coconut water and combination between 1g/L activated charcoal and 300 mL/L coconut water. The result showed that addition of activated charcoal and coconut water decreased viability of T. rafflesiae encapsulation. The result indicated that the use of MS (Murashige Skoog) medium with 4% sodium alginate and 50 mM CaCl2.2H2O formed synthetic seeds with high germination percentage (83%).Keywords : Tetrastigma rafflesiae, encapsulation, activated charcoal, coconut water